Leacock on life - Leacock, Stephen, 1869-1944 (University of Toronto Press, 2002)
Canadian cultural icon Stephen Leacock was as wise and witty as he was prolific, and as sharp as he was humane. A professor of political economy, author, and social critic, Leacock has long been considered Canada's foremost humourist and social satirist. He was at his best in observational humour but excelled as well in the unforgettable aphorism and the pointed riposte. Leacock's views on life provide a uniquely Canadian take on the world, an ironic perspective which continues to delight and instruct readers around the globe. Introduced and compiled by scholar and writer Gerald Lynch, with material gleaned from the approximately sixty books of fiction and non-fiction Leacock published, Leacock on Life is an anthology of Leacock's wit and wisdom, beginning with his memorable preface to Sunshine Sketches of a Little Town and ending with his bitter-sweet essay, 'Three Score and Ten.' With selections classified under forty-five headings and a reference key sourcing all quotations, this collection makes widely available Leacock's views on such subjects as: Canadian politics, love, education, economics, humour, technology, business, America, and writing, among many others. Leacock had opinions on every subject, and they are as humorous, provocative, and relevant today as when first articulated.